Wound closure and infection control - Editorial Staff, Editorial Staff (Operating Room Nurses Association of Canada Journal, 1987)
The skin stapler is a relatively recent innovation in wound closure systems - at least that's what many of us have been led to believe. The fact is, in ancient India, primitive people noted that a certain species of termite formed its nest by squeezing leaves together with their pincer-like heads and binding the leaves together.